MSMe Export Finance Go Internasional - Sri Hastutik; Sudarmiatin Sudarmiatin; Rosmiza Bidin (Green Publisher Indonesia, 2022)
The aim is to find out the obstacles that occur to MSMEs that go International in the payment of Kendang Djimbe's export finances and their settlement. Descriptive qualitative research method. This research wants to explore something new, which is not widely known by the public, so it wants to be studied more deeply. With the aim of describing the ongoing phenomenon when the research was carried out and examining the causes and effects of constrained export finance payments. The analytical tool used is fishbone analysis (Fishbone Diagram). Research sites on SMEs